Representation of Local Styles in Cingcangkeling Performance at the International Choir Festival as a Reflection of Sunda Cultural Identity - Gustina, Susi; Paz, Farhan Reza; Soeteja, Zakarias S. (Harmonia: Journal of Arts Research and Education, 2023)
This research was conducted to figure out the representation of local styles in Cingcangkeling performance at the international choir festival as a reflection of cultural identity. There are several studies on folksong, but generally, they only focus on music analysis; and do not explain the representation of local styles in folksong performances at the international choir festival. This research aims to figure out: a) the local style representation in the Cingcangkeling performance at international choir festivals; b ) the relationship between local styles represented in the Cingcangkeling performance with Sundanese cultural identity. It uses a qualitative method with a performance ethnographic approach as the design of the study which combines music and non-musical elements. The subject of this research is the Cingcangkeling performance (West Java) which was performed by PSM UPI at the 8th Bali International Choir Festival (BICF) in 2019. Data collection techniques were obtained through preliminary study, audio and video analysis, and interviews. The results of this study indicate that: 1) the representation of local styles in the Cingcangkeling song, both musically and non-musically, involves the bodor character (comedy) that is identical to Sundanese culture (West Java); 2) the choir does not only act as performers but also reflects the uniqueness and beauty of the Sundanese culture. The conclusion shows that the representation of local styles in the Cingcangkeling performance at international level festivals, both musically and non-musically, not only reflects Sundanese cultural identity but also shows the role of choir groups as ‘cultural ambassadors’ who introduce the uniqueness of Sundanese culture in the international world.